Inflation, economic growth and government expenditure nexus in South Africa - Valoyi, Sharlotte (My University, 2019)
The reality is that the South African GDP is not within the range of what is projected the previous years. As the proposed expenditure for 2017/18 totals R1.56 trillion according to the 2017 budget speech, the treasury also need to reduce spending by a total of R26 billion over the next two years. Economic growth continues to be below expected levels in South Africa and unemployment is very high. The relationship between inflation, economic growth and government expenditure is important in both developing and developed countries. Like in any other economy in the world, the South African government’s most important role is to promote economic growth, and also to sustain high economic growth with low inflation (Brand South Africa, 2015). The study is completely based on secondary data. The methodology is quantitative which includes econometrical tools. For this purpose, this study applied Augmented Dickey-Fuller (ADF) and Phillips Perron unit root tests, Choice of the lag length, Johansen-Juselius Co-integration analysis, VEC Granger Causality/Block exogeneity Wald test, Vector Error Correlation Model, Diagnostic tests, Stability tests, Impulse response and Choleski/Variance decomposition methodology. From the findings, the results derived by applying Johansen-Juselius Co-integration indicate that there is a longterm relationship between the rate of inflation, economic growth and government expenditure, and also that both government expenditure and inflation impact negatively on economic growth. The results indicate that government expenditure encourages inflation impacting negatively on investment and the country’s GDP. Granger causality runs jointly from all three variables inflation, government expenditure and investment to the dependent variable (economic growth)
Thesis(M.Com. (Economics)) -- University of Limpopo, 2019
Keywords: Inflation; Economic development; Government expenditure; Johansen Juselius co-integration analysis; South Africa; Inflation--South Africa; Economic development; Tax and expenditure limitations